Study on security of IPv6 address management in enterprise WLAN - Jarot, Sigit Puspito Wigati; Siddiqi, Mohammad Umar (s.n, 2012)

(untitled)
One-to-many reversible mapping is proposing a new scheme to enhance the security of IPv6 address management in an enterprise WLAN which ma be implemented into DHCPv6 software in stateful mode. Each time user try to access the network will be given different IP address to protect user privacy which will be generated using CFB mode of AES algorithm, however this dynamic address can be identified easily by the system